Dinamika Komunikasi Kesbangpol dan Ormas Islam dalam Membangun Kesadaran Kebangsaan di Kota Medan - Simatupang, Muhammad Andry; Kholil, Syukur (Medan Resource Center, 2024)
This study explores the interorganizational communication dynamics between the National Unity and Political Agency (Kesbangpol) and Islamic civil society organizations (Ormas Islam) in shaping national consciousness in Medan, Indonesia. It focuses on how organizational structures, symbolic practices, and power relations influence the transmission and reception of civic values within a multireligious and multicultural urban setting. Using a qualitative case study with a critical-interpretive paradigm, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that communication between Kesbangpol and Ormas is largely top-down, symbolic, and lacking in dialogical depth. Symbolic representations of nationalism are often framed rhetorically without substantial internalization, and civic values tend to be disseminated through formalized rituals rather than sustained engagement. The study concludes that current practices are insufficiently participatory and require a shift toward deliberative communication, mutual recognition, and cultural sensitivity to support inclusive and sustainable civic engagement. This research contributes theoretically to the discourse on state–civil society relations by highlighting the limitations of symbolic governance, and offers practical insights for designing more dialogic and culturally responsive civic communication frameworks.